THE PHENOMENON OF RELIGIOUS FAITH: THEOLOGICAL, PHILOSOPHICAL AND RELIGIOUS STUDIES INTERPRETATIONS - Sviatoslav Kyiak (Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the phenomenon of faith addressed from the perspective of theology, philosophy and religious studies. The central role of faith in the Christian religion is highlighted, as well as the specifics of the phenomenon in the 20th - early 21st century Catholicism. The general theoretical approaches to the phenomenon of religious faith in the works by national and world philosophers, theologians and religious studies scholars are reviewed; the paper highlights the principles of their theories based on rational interpretation of the premises of faith, Christian virtues, which underlie moral, ethnic and social norms in particular.